Variation in the Biochemical Composition of the Edible Seaweed Grateloupia turuturu Yamada Harvested from Two Sampling Sites on the Brittany Coast (France): The Influence of Storage Method on the Extraction of the Seaweed Pigment R-Phycoerythrin. (26th February 2013) - Munier, Mathilde; Dumay, Justine; Morançais, Michèle; Jaouen, Pascal; Fleurence, Joël
Abstract : Numerous studies have demonstrated that the biochemical content of seaweeds varies according to seasonality in a restricted area. In this study, the influence of sampling site on the biochemical composition of the edible red seaweed Grateloupia turuturu Yamada was investigated, but not its variation over time. Some differences in water-soluble protein (7.19 ± 0.74 mg · g - 1 dw and 19.15 ± 0.47 mg · g - 1 dw), water-soluble carbohydrate (16.05 ± 0.82 mg · g - 1 dw and 41.57 ± 0.66 mg · g - 1 dw), and lipid contents (28.07 ± 5.12 mg · g - 1 dw and 54.35 ± 2.05 mg · g - 1 dw) were recorded between the two sites chosen on the Brittany coast (France). The yield of R-phycoerythrin (R-PE) contained in the seaweed also varied according to the sampling site (1.16 ± 0.33 mg · g - 1 dw versus 4.39 ± 0.15 mg · g - 1 dw). In addition, the effect of storage conditions on the preservation of R-PE was studied. The results demonstrated that freezing is the best preservation method in terms of R-PE extraction yield and purity index. In conclusion, this study shows that the sampling site influences the biochemical content of the red seaweed Grateloupia turuturu . Moreover, the extraction yield of R-phycoerythrin and its purity index depend on both the sampling site and the sample storage method.